The Effect of Acupressure and Lavender Aromatherapy on Breast Milk Production and Uterine Involution in Post Partum Mothers - Kurniyati; Wenny Indah Purnama Eka Sari; Kartinazahri; Yusnaini; Derison Marsinova Bakara (Postgraduate, University of Mataram, 2026)
During the postpartum period, two processes occur: uterine involution and lactation. Acupressure can help maximize prolactin and oxytocin receptor activity, minimize the side effects of delayed breastfeeding in the baby, and influence oxytocin release, which triggers uterine muscle contractions and retraction, thereby accelerating uterine involution. Lavender aromatherapy induces a relaxing effect through the central nervous system, which can help increase oxytocin production—a hormone that plays a role in boosting breast milk production—and triggers uterine contractions to accelerate uterine involution. The objective of this study is to determine the effects of acupressure and lavender aromatherapy on breast milk production and uterine involution in postpartum mothers before and after intervention. The study used a quasi-experimental pretest-posttest design with a control group. The population consisted of breastfeeding postpartum mothers at the PMB in Curup City, Rejang Lebong Regency, and the PMB in Aceh Besar City. The sample was selected using simple random sampling and included 82 respondents divided into two groups of 41 each. The research instrument consisted of a questionnaire designed to gather information about the respondents' characteristics, as well as an observation sheet to monitor breast milk production and assess uterine involution. The acupressure therapy intervention involved applying pressure to three specific points: Large Intestine 4 (LI 4), Stomach 36 (ST 36), and Small Intestine 1 (SI 1). This was complemented by the use of lavender aromatherapy. The study results indicated that both acupressure and lavender aromatherapy had a significant impact on breast milk production and uterine involution (P ≤ 0.05). Overall, the administration of acupressure and lavender aromatherapy proved to be effective in enhancing breast milk production and promoting faster uterine involution in postpartum mothers.